2020
DOI: 10.1021/acs.inorgchem.0c02499
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent salen-type Zn(II) Complexes As Probes for Detecting Hydrogen Sulfide and Its Anion: Bioimaging Applications

Abstract: In this work, we investigate the mode of interaction of a family of fluorescent zinc complexes with HS − and H 2 S. Different experiments, performed by diverse spectroscopic techniques, provide evidence that HS − binds the zinc center of all the complexes under investigation. Treatment with neutral H 2 S exhibits a markedly different reactivity which indicates selectivity for HS − over H 2 S of the systems under investigation. Striking color changes, visible to the naked eye, occur when treating the systems wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…[24][25][26][27][28][29] Among Zn(salen)-type complexes, colourful derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are certainly those more interesting for their optical absorption and fluorescence emission properties upon deaggregation. [30][31][32][33][34][35][36][37] In order to further explore these varied characteristics, we have chosen a Zn(salmal) complex, 1, having different substituents on the salicylidene rings. In particular, we found that the presence of 5-tert-butyl-bulky substituents makes this complex sufficiently soluble in a range of coordinating/non-coordinating solvents, giving us the possibility to explore its spectroscopic properties in solution, even in comparison to previous studies on amphiphilic Zn(salmal) complexes with longer alkyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Among Zn(salen)-type complexes, colourful derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are certainly those more interesting for their optical absorption and fluorescence emission properties upon deaggregation. [30][31][32][33][34][35][36][37] In order to further explore these varied characteristics, we have chosen a Zn(salmal) complex, 1, having different substituents on the salicylidene rings. In particular, we found that the presence of 5-tert-butyl-bulky substituents makes this complex sufficiently soluble in a range of coordinating/non-coordinating solvents, giving us the possibility to explore its spectroscopic properties in solution, even in comparison to previous studies on amphiphilic Zn(salmal) complexes with longer alkyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] In particular, derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are characterized by relevant optical spectroscopic changes in relation of the nature of the aggregate species or monomeric adducts. [47][48][49][50][51][52][53] We have demonstrated that in solution of weak coordinating solvents a 5-tert-butyl substituted Zn(salmal) complex (1) forms relatively stable adducts which easily transmetalate with divalent ions of the first transition series, but with a different rate. 54 In particular, the transmetalation with Cu 2+ ions is faster than that with other cations, regardless of the nature of the counteranion.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8b , 8d ] This effect was used previously for bioimaging and biosensing in living cells. [ 8c , 8g , 9 ] Furthermore, derivatives of this zinc(II) complex type were investigated for their mechanochromic luminescence behavior, and as emitters for optical temperature sensing via thermally activated delayed fluorescence (TADF). [10]…”
Section: Introductionmentioning
confidence: 99%